Psychosocial Aspects of Hip Disease in the Young Adult. Issue 4 (July 2013) - Nisar, Aamer; Augustine, Angela; Horrey, Lynne; Craig, David; Meek, Robert M. D.; Patil, Sanjeev
The psychosocial impact of hip disease on the young adult has not been elucidated. This study aimed to identify the functional and psychosocial characteristics of a cohort of young patients (age less than 40 years) presenting to our tertiary care complex hip clinic. A postal questionnaire comprising of a Visual Analogue Scale (VAS) for Pain, the Oswestry Disability Index (ODI) and the Hospital Anxiety and Depression Scale (HADS) was posted to 63 patients. Forty-nine (n = 49) patients (79%) responded to the questionnaire. Mean age was 20 years (range 16-38) with a gender ratio of 2:1 (female: male). More than half of our patients had moderate to severe pain based on the VAS and at least moderate disability on the ODI. HADS showed that 32% and 49% of patients were classified as having borderline to abnormal levels of depression and anxiety respectively. Multiple regression showed ODI scores to be a significant predictor of anxiety and depression. Comparison with asymptomatic controls shows that these patients have significantly worse ODI and HADS scores compared to normal population. This study quantifies the degree of functional and psychosocial compromise present in young patients with hip problems.